ANALYSIS OF INTELLECTUAL CAPITAL TO INCREASE BUSINESS PERFORMANCE (SURVEY ON PT. TELEKOMUNIKASI INDONESIA, TBK WITEL SULSEL) - Dian Parawansa; Andi Aswan; Marry Fusfita (Journal of Risk and Uncertainty Issues, 2023)
This study aims to investigate the influence of dominant factors of intellectual capital: human capital, customer capital and structural capital to business performance as a test of the theory and models of Bontis et. al. (non monetary), with the surveyed private firms On PT. Telekomunikasi Indonesia, Tbk Witel Sulsel. The importance of intellectual capital is now considering that the company has begun to consider intellectual capital to distinguish intangible, intangible company's assets where assets are not only gained by spending some money but can also be used and make a profit. The respondents in this study were as 120 employees. The analysis technique used to test the hypothesis is factor analysis. The results showed that the three independent variables,